The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.21608/jpp.2014.64749
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Population and Distribution on Yield and Yield Components of Five Faba Bean Genotypes

Abstract: Plant population density plays an important role on crop growth and yield as response to light penetration and photosynthesis rate. A field experiment was carried out at Sids Research Station, Agricultural Research Center (ARC), during two successive winter seasons, of 2012/13 and 2013/14. The objectives of this investigation was aimed to evaluate five faba bean genotypes namely Nubaria 1(large seeded cultivar), Giza 429, line 43130, E.19 (medium seeded types) in addition to the small seeded type Camolina. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…However, the highest seed yield/fed resulted from sowing faba bean at plant population 120000 plants/fed which exhibited increments of seed yield by 18.30 and 5.30% in the first season as well as 19.53 and 8.51 % in the second season than that of 80000 and 96000 plants/fed, respectively (Table 3). These results are in agreement with thus reported by El-Hindi et al, 2008 andAbd El-Rahman, 2014). Narrow ridges spacing may increase crop access to available soil moisture because of the more equidistant distribution of crop plants and increases light interception by the crop, particularly in the early growing season, thereby leading to increased crop growth rates and earlier canopy closure, Dalley et al (2004).…”
Section: Yield and Its Attributessupporting
confidence: 92%
See 1 more Smart Citation
“…However, the highest seed yield/fed resulted from sowing faba bean at plant population 120000 plants/fed which exhibited increments of seed yield by 18.30 and 5.30% in the first season as well as 19.53 and 8.51 % in the second season than that of 80000 and 96000 plants/fed, respectively (Table 3). These results are in agreement with thus reported by El-Hindi et al, 2008 andAbd El-Rahman, 2014). Narrow ridges spacing may increase crop access to available soil moisture because of the more equidistant distribution of crop plants and increases light interception by the crop, particularly in the early growing season, thereby leading to increased crop growth rates and earlier canopy closure, Dalley et al (2004).…”
Section: Yield and Its Attributessupporting
confidence: 92%
“…Consequently, a greater photosynthetic photon flux density interception with a lower weed aboveground dry matter were recorded with narrow row arrangement. Similar results were reported by (Farghaly, 2002;El-Hindi et al, 2008 andAbd El-Rahman, 2014) The results presented in Table 1 clearly showed that the dry weights of broadleaved, grassy and total weeds were significantly reduced due to studied weed control treatments as compared with the unweeded check. Two hand hoeing method recorded the highest weed depression expressed in the lowest dry matter of the mentioned weed groups.…”
Section: A Weed Growthsupporting
confidence: 88%
“…Particularly, Turco et al (2016) found that faba bean seeds contain several other bioactive compounds, such as polyphenols. However, the effect of faba bean plant density on growth, yield and its attributes was studied by Bakry et al (2011), Khalil et al (2011) and Abd El-Rahman (2014). Growing faba bean in two sides per row produced higher seed yield per unit area than one side per row (Abou-El-Seba et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with this study, ref. [ 37 ] and ref. [ 38 ], who reported significant differences of grain yield among varietal performance.…”
Section: Discussionmentioning
confidence: 99%